Endoscopic resection of early esophageal neoplasia in patients with esophageal varices: a systematic review - Frederiks, Charlotte N.; Boer, Laura S.; Gloudemans, Bas; Alvarez Herrero, Lorenza; Bergman, Jacques J.G.H.M.; Pouw, Roos E.; Weusten, Bas L.A.M. (Endoscopy, 2025)
Although endoscopic resection (ER) is recommended as first-choice treatment for early esophageal neoplasia, patients with esophageal varices are considered a high-risk group owing to an increased risk of bleeding. This systematic review aimed to evaluate the effectiveness and safety of ER in this specific patient category.We searched for studies reporting on clinical outcomes of ER in the presence of esophageal varices, irrespective of study design or follow-up time. End points included the incidence of prophylactic measures to reduce the risk of variceal hemorrhage, radical and curative resection rates, and adverse events.After screening 2371 studies, 42 studies (including our own unpublished cohort) with a total of 186 patients were included in this systematic review. Endoscopic band ligation (72/186; 39%) and endoscopic injection sclerotherapy (22/186; 12%) were the prophylactic measures most widely adopted to eradicate varices prior to ER. Other frequently described prophylactic measures included direct varix coagulation during ER (18/186; 10%) and the placement of a transjugular intrahepatic portosystemic shunt prior to ER (9/186; 5%). While the radical and curative resection rates were high (86% and 72%, respectively), the periprocedural and delayed bleeding risks were reported to be relatively low (6% and 3%, respectively). In all studies, no procedure-related mortality was observed.ER appeared to be a safe and effective treatment option in selected patients with concurrent early esophageal neoplasia and esophageal varices, provided that a tailored approach of adequate prophylactic measures to prevent bleeding is applied.